Corporate governance network around social responsibility and activism against the Sustainable Development Goals - Crespo, Julio E.; García Lirios, Cruz; Vélez Báez, Sonia Sujell; Rincón Rodríguez, Isabel Cristina; Chaparro Medina, Jorge E.; Meriño Córdoba, Víctor Hugo; Sánchez Sánchez, Arturo; Quiroz Campas, Celia Yaneth; Molina González, María del Rosario (Heritage and Sustainable Development, 2024)
The social responsibility aspect of corporate governance is intricately linked to the Sustainable Development Goals, particularly around SDGs 5, 8, 9, and 12. Corporations and companies play a direct and crucial role in achieving these goals. The current state-of-the-art literature often emphasizes the financial aspect without delving into the dimensions that ensure the achievement of these goals. Therefore, the significance of this work lies in its objective to establish a comparative analysis of the findings related to the SDGs reported in the literature and their evaluation by experts in corporate governance and social responsibility. This research, which was documentary, transversal, exploratory, retrospective, and correlational, was conducted with a sample of judges selected for their experience, knowledge, and criteria for evaluating summaries published in journals indexed in international repositories. The results reveal the financial category as the only discrepancy, with the present work considering it as an external factor to corporate governance, unlike the state-of-the-art literature that highlights it as a central node. As a result, we recommend the inclusion of the financial dimension in the analysis of neural networks to establish the degree of learning in this area once the pandemic has passed.